2010
DOI: 10.1007/s00216-009-3387-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a fast screening method for the detection of cocaine in hair by MALDI-MS

Abstract: The sensitivity and specificity of a novel method of screening for cocaine in hair, based on matrix-assisted laser desorption/ionisation (MALDI) mass spectrometry (MS), have been evaluated. The method entails a rapid extraction procedure consisting of shaking 2.5 mg pulverised hair at high frequency in the presence of an acidic solution (160 microL of water, 20 microL of acetonitrile and 20 microL of 1 M trifluoroacetic acid) and a stainless-steel bullet. Following centrifugation, the supernatant is dried unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 17 publications
0
26
0
1
Order By: Relevance
“…Other examples of univariate methods based on visual and instrumental signals can be found elsewhere [2,[37][38][39].…”
Section: Cases Studymentioning
confidence: 99%
“…Other examples of univariate methods based on visual and instrumental signals can be found elsewhere [2,[37][38][39].…”
Section: Cases Studymentioning
confidence: 99%
“…This is solved when using liquid chromatography with traditional detectors [6,18,22,29], or coupled to different mass spectrometry detectors as triple quadrupole [23,24], ion trap [15], time-of-flight mass spectrometry [14] or hybrid linear ion trap-orbitrap mass spectrometry [31,32]. The use of direct mass spectrometric techniques such as ambient ionization mass spectrometry [33] and Matrix-Assisted Laser Desorption Ionization Mass Spectrometry (MALDI-MS) [34] have been also described for drug testing in hair extracts.…”
Section: Introductionmentioning
confidence: 99%
“…For drugs in hair, Vogliardi et al [14] recently attempted direct detection of cocaine and its metabolites in hair using MALDI-MS with various sample preparation methods, including pulverization and extraction. However, they concluded that the extraction of analytes by incubating hair (preferably pulverized) in an acidic solvent was necessary, and demonstrated that the application of MALDI-MS to direct detection of drugs in hair is difficult [15] because of their low concentrations (ng/mg levels) and strong binding to the hair matrix [3][4][5].…”
Section: Introductionmentioning
confidence: 99%